«Degdar» PO (Eurasian Journal of Philology Science and Education, 2016)
The article deals with the life and creative activity of the famous writer of foreign literature of Edgar Allan Poe. It is said that Edgar Allan Poe made his first step in the literature as a poet, how have been published his first collection of poems. However, the first step in the literature was not particularly successful, but in spite of his poem, which was written by him in 19 years you can see that it was full of Western and Eastern literature, knew well and had a deep knowledge of history. Also, the article says that the fate of the writer there was not a smooth birth. But despite the difficulties in life, it takes place in ososboe literature. More in the article there is information that after his death were some of the events relating to his life.
Keywords: literature; writer; poet; life; father; poem; story.